Investigating a novel application for magnetic biochar: Practical barriers and policy considerations - Gillingham, Max (2024)
Biochar, a carbonaceous sorbent material which can be sustainably produced from agricultural and food waste, is a highly relevant material in the field of environmental research, offering potential routes for improving soil fertility, sequestering carbon and removing pollutants from land and water. While the benefits of biochar are known in some contexts, there remain certain barriers to its wider use at large scales, as well as in the use of modified biochar. One example of this is the use of magnetic biochar for soil remediation, whereby pollutant-laden biochar could be removed and recycled from soil using magnetic extraction. This thesis firstly reviews the challenges and opportunities for such a strategy, using research data from multi-disciplinary studies, with a focus on overcoming the practical barriers to its development. The evidence suggests that the strategy is viable, but research gaps must first be addressed to ensure it is safe and cost-effective. Secondly, the ability to magnetise medium (1.70 – 3.55 mm) and large (>3.55 mm) biochar particles for soil application, in contrast to previous studies which use small particles and powder, is investigated through performing a chemical co-precipitation reaction, with subsequent surface analysis by Scanning Electron Microscopy with Energy-dispersive X-ray Spectroscopy (SEM-EDS) and Attenuated Total Reflection Fourier Transform Infrared Spectroscopy (ATR-FTIR). The results showed that medium and large biochar particles exhibit magnetic properties after the co-precipitation method of magnetisation, but the effect is much stronger in the medium size particles. The SEM-EDS analysis identified the presence of iron oxide particles across the surface of magnetic biochar, while ATR-FTIR confirmed the presence of Fe-O bonds on the magnetic biochar surface, providing a reliable technique for assessing and comparing the results of magnetisation reactions. However, potential practical issues in scaling up such a method for use in the system proposed in chapter two are identified and discussed. Finally, outcomes of the literature review and experimental work are discussed in the context of UK policy opportunities and barriers.